Seikat pisang: integrated media in photography - Samsudin, Fahmi; Mohamad Khalil, Musaddiq; Sulaiman, Shaharin (2024)
Humankinds are multicellular organism, where each specialized cells performs various functions, integrating as unique building blocks identical to the whole-system. Integration of media in photography can also be viewed similar, in a dynamic spirit towards creativity, as well as visual expressions. The convergence between imaginations (ideas) of the ‘noumena’ and reality of the ‘phenomena’ is well conceived as a symbiotic process, in regards to how the photographer maneuvers his/her narrative in visual making, through ‘light’, and ‘lens’ of an integrated tool identified as a ‘Camera’. In the history of photography, as early as the 400BC, the technical aspects which lays the foundational attributes of photography as we experience today, was develop through the principles of the ‘Camera Obscura’, described as well as developed by philosophers and scholars such as; Mozi from the east, Aristotle from the west, and Alhazen from the Middle-East.